Resident satisfaction with the pediatric surgery training program - Altokhais, Tariq (BMC Med Educ, 2020)
BACKGROUND: The pediatric surgery residency program is new in Saudi Arabia. As with any new program, residents experience a degree of fear and anxiety about their future in the program. The aim of this study is to examine residents’ satisfaction with the program. METHODS: This study included an online survey examining residents’ satisfaction. It consisted of demographic, financial, personality, program-specific, and burnout assessment questions. All questions were multiple-choice items. Descriptive statistical data are presented as frequency distributions and percentages. Cross-tabulations and chi-square tests were used at the bivariate level of analysis to compare subgroups and identify factors of satisfaction. Binary logistics regression was used at the multivariate level of analysis to compute the odds ratio of significant variables. RESULTS: Thirty-one out of 32 residents responded to the survey. The multivariate logistic regression showed that current year of residency, current relationship status and personality statistically affected the satisfaction of residents. Senior residents, i.e., residents who had spent four years or more in the program, were 40 times more likely to be satisfied than were residents in their first year; residents who were married were more than eight times more likely to be satisfied than were residents who were single; and residents who were neutral or who agreed that they were very indecisive were 8% less likely to be satisfied than were those who reported being decisive. Gender was statistically significant, such that males were more satisfied than females were. CONCLUSIONS: Although the pediatric surgery residency program is new, this survey has shown that there is generally a high rate of satisfaction. Satisfaction was also observed more in senior residents. Further studies should be conducted in the future when residents graduate from the program.